Physicochemical properties, chemical components, and antibacterial activity of the essential oil from Mentha arvensis L. leaves - L.P.T. Quoc (Учёные записки Казанского университета: Серия Естественные науки, 2022)
Essential oil (EO) obtained from Mentha arvensis L. leaves was separated by the steam distillation method. The following EO physicochemical properties were analyzed: acid value, saponification value, ester value, relative density, absolute density, and freezing point. Using gas chromatography-mass spectrometry, 26 major compounds were detected in the EO, with menthol having the highest level (69.44%). The antioxidant capacity of the EO (IC50 = 330 mg mL–1) was determined with the help of the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The antibacterial activity (against Salmonella enteritidis, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli) was assessed using the paper disc diffusion method for antibiotic susceptibility testing.